Algehele grondwetsherziening : (Staatsuitgeverij, 1979)
1:Grondrechten . - 1979-. - bdn - (Naar een nieuwe grondwet ; 15,) a: Klassieke grondrechten ; sociale grondrechten. - 1979. - XV, 547 p. - Index. - ISBN 90-12-02672-5